Peritoneal gliomatosis in ovarian teratoma: a brief review of the literature and a case report - A. Yu. Shamanova; V. V. Saevets; S. V. Khohlova; G. V. Sychugov; K. S. Aristarkhova; L. V. Yarina; Yu. V. Klyuchnik (ABV-press, 2023)
Malignant neoplasms of the pelvic organs and abdominal cavity are often associated with peritoneal gliomatosis (PG). Detection of PG and its differentiation from carcinomatosis and other changes in the tissue using ultrasound, magnetic resonance imaging, computed tomography is extremely limited. Questions of the pathogenesis of PG, its influence on the course of the main tumor process, as well as the relationship with indicators of overall and relapse-free survival remain debatable. We believe that the description of the PG encountered in practice is extremely relevant in the aspect of considering the possibility of the presence of such a pathology in the tumor process and the inclusion of PG in the differential diagnostic series in the diagnosis of changes in the omentum and peritoneum of the small pelvis and abdominal cavity using various methods (ultrasound, magnetic resonance imaging, intraoperative urgent histological examination).